Enhancing Seawater Salinity through Spray-Assisted Evaporation: Investigating the Effect of Nozzle Sprayer Diameter and Feed Flowrate on Evaporation Rate using Multiple Regression Analysis - Lilik Suprianti; Nove Kartika Erliyanti; Soemargono Soemargono; Yehezkiel Hesed Providensia; Stefanus Dady Waluyo (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Salt production plays a vital role in life due to its essential minerals. Traditional salt production methods using direct solar rays are the most common in Indonesia. It needs a large area and several weeks extended to evaporate sea water into concentrated brine. It is very weather dependent. This study investigates the utilization of a spray-assisted evaporator to increase the salinity of seawater for salt production. The experimental setup consisted of a custom-designed spray evaporator that atomized seawater into fine droplets. A series of experiments were conducted to analyze the effect of different operational parameters, including feed flow rate (1000 ml/min; 1200 ml/min; 1400 ml/min; 1600ml/min; 1800ml/min) and diameter of nozzle sprayer (1 mm; 2 mm; 3 mm) on the average of evaporation rate. The results demonstrated that Higher spray flow rates and smaller droplet sizes positively correlated with increased evaporation rates, leading to higher salt concentrations in the collected brine. Optimizing the Impact of nozzle sprayer diameter and flow rate on the average evaporation rate utilizing multiple linear regression and deriving the Equation ,where x1 represents the seawater feed flow rate, and X2 represents the nozzle sprayer diameter.